Propriedades físico-químicas, estruturais e tecnológicas de extratos colagênicos de diferentes partes do coelho - Toniasso, Daniela Pedrolo Weber (2020)
Rabbit meat, although not widespread in Brazil, has gained considerable importance since rabbit meat is healthy, has less fat, in addition to the high prolificity of the animal in a short time and the possibility of using its by-products. These by-products are often not used and are sent incorrectly in the environment. Therefore, obtaining collagen is a promising alternative to add value to them. Collagen can be obtained by chemical or enzymatic hydrolysis, and the most advantageous and with the highest yield is enzymatic through the use of proteolytic enzymes such as papain and pepsin. In view of the above, this study aimed to isolate and characterize collagen in rabbit meat, skin and ear. Collagen extracted with pepsin obtained a good yield, the triple helical structure remained intact, which can be confirmed by the analysis of infrared spectroscopy with Fourier transform (FTIR), and by electrophoresis (SDS-PAGE), where the collagens were constituted basically by type I collagen. As for technological properties, collagens exhibited high solubility in acid pH and low solubility in high pH (alkaline), the emulsifying activity index was higher than that found for bovine bone gelatin. In addition, the collagen foaming was relatively low when compared to literature data, however, its stability was high. It is concluded that the studied rabbit raw materials can be a viable source for collagen extraction, being used as an alternative source to bovine and swine collagen, in addition to adding value to meat and by-products of rabbit farming